Concussion Symptom Cutoffs for Identification and Prognosis of Sports-Related Concussion: Role of Time Since Injury. Issue 10 (August 2020) - Eagle, Shawn R.; Womble, Melissa N.; Elbin, R.J.; Pan, Raymond; Collins, Michael W.; Kontos, Anthony P.
Background: Symptom reporting with scales such as the Post-Concussion Symptom Scale (PCSS) is one of the most sensitive markers of concussed status and/or recovery time, It is known that time from injury until initial clinic visit affects symptom presentation and recovery outcomes, but no study to date has evaluated changes in clinical cutoff scores for the PCSS based on earlier versus later clinical presentation postconcussion. Purpose: To evaluate if time since injury after sports-related concussion (SRC) affects clinical cutoff scores for total PCSS and PCSS factors in differentiating athletes with SRC from healthy controls and predicting prolonged recovery (>30 days) after SRC. Study Design: Cohort study; Level of evidence, 3. Methods: A chart review was conducted of clinical data from patients with SRC (age, 13-25 years; n = 588; female, n = 299) who presented to concussion specialty clinics. Participants were categorized on the basis of time from injury: early (≤7 days; n = 348) and late (8-21 days; n = 240). Outcomes were total symptom severity (ie, total PCSS score) and total score for each of 4 symptom factors (cognitive/migraine/fatigue [CMF], affective, sleep, and somatic). Area under the curve (AUC) analyses were conducted using the Youden index to optimize sensitivity and specificity cutoffs. Results: In the early group, the CMF factor (cutoff, ≥7; AUC = 0.944), affective factor (cutoff, ≥1; AUC = 0.614), and total PCSS (cutoff, ≥7; AUC = 0.889) differentiated athletes with SRC from controls. In the late group, the CMF factor cutoff was reduced (cutoff, ≥4; AUC = 0.945), while the total PCSS score (cutoff, ≥7; AUC = 0.892), affective factor (cutoff, ≥1; AUC = 0.603), and sleep factor (cutoff, ≥1; AUC = 0.609) remained the same. In the early cohort, the CMF factor was the strongest predictor of protracted recovery (cutoff, ≥23; AUC = 0.717), followed by the total PCSS (cutoff, ≥39; AUC = 0.695) and affective factor (cutoff, ≥2; AUC = 0.614). The affective factor (cutoff, ≥1; AUC = 0.642) and total PCSS (cutoff, ≥35; AUC = 0.592) were significant predictors in the late cohort, but the cutoff threshold was reduced. Conclusion: The findings indicate that PCSS symptom clinical cutoffs for identifying injury and recovery prognosis change on the basis of time since injury. Specifically, the combination of CMF, affective, and sleep factors is the best differentiator of athletes with SRC from controls regardless of time since injury. Furthermore, the CMF factor is the most robust predictor of prolonged recovery if the patient is within 1 week of SRC, whereas the affective factor is the most robust predictor of prolonged recovery if the patient is within 2 to 3 weeks of SRC.